Association of Serum Lipid Levels with Parkinson’s Disease: A Case-Control Study (Bangladesh Journal of Neuroscience, 2018)
Background: Parkinson’s disease (PD) is a common neurodegenerative disorder. Many hypotheses have been put forward for PD pathogenesis including role of lipid metabolism.Methods: This case control study was carried out in the department of neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from April 2018 to September 2019. A total of 90 persons were enrolled as study population after satisfying inclusion and exclusion criteria. Among them, 42 PD patients were grouped as cases and 48 healthy persons were controls.Results: We have compared the mean (±SD) value (mg/dl) of serum lipid variables among the cases and the controls. Serum total cholesterol in PD patients was found lower than that of control group (176.88 ± 41.12 vs 209.27 ± 43.69 mg/dl) which was statistically significant (p = 0.001) and mean (±SD) value (mg/dl) of serum LDL-C in PD patients was also found significantly lower than that of control group (107 .44 ± 39.04 vs 127.40 ± 37.83 mg/dl, p = 0.017). Serum TG levels were also significantly lower among PD patients than that of controls (152.40 ±77.86 vs 206.71 ±94.76 mg/dl, p = 0.04). Serum high-density lipoprotein cholesterol (HDL-C) levels were statistically similar among cases and controls (39.81 ± 9.79 vs 39.33 ±12.21 mg/dl, p = 0.840).Conclusion: There is an association between low serum TC, LDL-C and TG levels with PD. Further prospective studies are necessary to confirm the association.Bangladesh Journal of Neuroscience 2018; Vol. 34 (2): 66-71